Removal of iron contaminant from Sabah montmorillonite using gravitational & extraction techniques - Sonny, Irawan; Samsuri, Ariffin (2004)
The removal of iron contaminant from Sabah montmorillonite mineral by combination of gravitational method and organic extraction (oxalic acid) technique has been studied under various experimental conditions in order to optimize the process parameters at minimum operating cost. The parameters studied were pressure drop, airflow rate, temperature, pH of the solution, organic acid concentration, and time of extraction. For the Sabah montmorillonite sample studied, at airflow rate of 18 m.cu/hr the optimum pressure drop was 231 N/m/sq., has separated 60 % by weight of iron contaminant from montmorillonite, and at temperature vary between 60 - 80 deg. C, the maximum iron contaminant extraction with oxalic acid is approximately 30%. Oxalic acid is capable of dissolving all extracted iron in montmorillonite. Combination with gravitational and oxalic acid extraction technique successfully removed 90 % of iron contaminant from Sabah montmorillonite, thus making Sabah montmorillonite suitable for its basic industrial application.